2019
DOI: 10.3390/cancers11050660
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3 Mutations: An Updated View of Their Role in Chromatin Deregulation and Cancer

Abstract: In this review, we describe the attributes of histone H3 mutants identified in cancer. H3 mutants were first identified in genes encoding H3.3, in pediatric high-grade glioma, and subsequently in chondrosarcomas and giant cell tumors of bone (GCTB) in adolescents. The most heavily studied are the lysine to methionine mutants K27M and K36M, which perturb the target site for specific lysine methyltransferases and dominantly perturb methylation of corresponding lysines in other histone H3 proteins. We discuss rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 135 publications
2
95
0
1
Order By: Relevance
“…H3.3 has recently received much attention because a high frequency of mutations in H3.3 genes have been identified in pediatric brain and bone cancers (Behjati et al, 2013;Lan and Shi, 2015;Lowe et al, 2019;Schwartzentruber et al, 2012a;Wan et al, 2018;Wu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H3.3 has recently received much attention because a high frequency of mutations in H3.3 genes have been identified in pediatric brain and bone cancers (Behjati et al, 2013;Lan and Shi, 2015;Lowe et al, 2019;Schwartzentruber et al, 2012a;Wan et al, 2018;Wu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies have directly linked histone variant H3.3 to oncogenesis. Sequencing studies revealed a high frequency of mutations in H3.3 genes in several cancer types including pediatric high-grade glioblastoma and bone tumors (Lowe et al, 2019;Schwartzentruber et al, 2012a;Wu et al, 2012;Yuen and Knoepfler, 2013). Downregulation of H3.3 expression in adult glioblastoma has been found to disrupt chromatin organization and promote cancer stem cell properties (Gallo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, H3G34 mutations promote genome instability and possibly tumorigenesis by impeding MMR activity. Besides these known results, one very interesting hypothesis is that whether the G34R mutation itself would generate a new site for methylation on the histone tail [94].…”
Section: H3k36me3 Associated Ddr In Tumorigenesismentioning
confidence: 99%
“…Indeed, H3K27me3 increases in the intergenic regions where the H3K36me2 is decreased in the H3.3K36M mutate cells [97,98]. How this H3K36M mutation controls DNA damage repair is still unknown [94,99]. More efforts should be placed to discover the detailed molecular mechanisms of how oncohistones promote tumorigenesis through DNA damage repair pathways.…”
Section: H3k36me3 Associated Ddr In Tumorigenesismentioning
confidence: 99%
“…The generation of PGCCs is the result of cell fusion process which is considered as an important factor for cancer progression [29]. It has been confirmed that several chemotherapeutic drugs which are used to block mitosis help in the acceleration of giant cancer cell formation, these cells are usually shown to be susceptible to the holocaust involved in mitosis along-with the later step for apoptotic process in a sequential manner [30]. PGCCs may undergo the process of budding and bursting in order to give birth to the daughter cells.…”
Section: Polyploid Giant Cancer Cells (Pgccs)mentioning
confidence: 99%